Evaluation of body condition score at livestock judgement of Holstein-Friesian cows - Mikó Józsefné Jónás, Edit; Mucsi, Imre; Komlósi, István (Animal welfare, Ethology and Housing Systems (AWETH), 2011)
The body condition scoring also has been part of the livestock judgement in Hungary since 2007. The authors analyzed the connection between the main functional areas and the linear condition score at livestock judgement. The results of livestock judging were processed from the data of two large scale dairy farms. Livestock judging was done by the expert of the Holstein-Friesian Breeders Association. The data of relationship were analysed separately in the first, second and third lactation. A total of 2472 judgement results were processed.To sum up the results of their work they came into the conclusion that the scores of the body capacity in case of the main judgement features were higher in cows, which calved more times than in the first- lactation-cows. The score of body increases, while the score of the legs and the udder decrease with the growing number of lactations. The dairy character and the final class did not depend on the number of lactations.The condition influenced the evolution of the score of body positively, but there is only a loose correlation between these two parameters (r = 0.06 – r = 0.20). They found negative correlation with the dairy character (r = -0.45 – r = -0.57). The most scores for dairy character were given to the cows that obtained only two, three or perhaps four linear score at the body condition scoring.Based on these results they suggest that livestock judgement should be made later, probably in the 5-6th month of the lactation.
Keywords: Holstein-Friesian; livestock judgment; body condition scoring